PROFILE OF LUNGS VOLUME IN THE DIABETES MELITUS AND NON DIABETES MELITUS - Litta Marlin Patty; Jodelin Muninggar; Nur Aji Wibowo (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
International Diabetes Federation states that in 2007 there were 246 million people in the world suffering from diabetes and it is expected to increase to 380 million by 2025. DM can cause susceptibility to infections in the human lung organs due to hyperglycemia. The purpose of this study was to determine the lung volume profile in the form of VT, VCI, VCE and VKP in the DM group and non DM group. This study uses a quantitative descriptive survey design with a sample of 60 people, consisting of 30 people from the DM group and 30 people from the Non DM group. The statistical test used in this study is the Independent statistical sample t-test, the Mann-Whitney test and the Pearson correlation. The results showed: (1) There was a significant difference in the DM of the DM group and the Non DM group with p = 0.021 (p <0.05); (2) There were significant differences in VT, VCI, VCE of the DM group and Non DM group with significant values ​​of VT (p = 0,000 <0.05), VCI (p = 0.003 <0.05) and VCE (p = 0.001 <0.05); (3) There was no significant difference in the VKP of the DM group and the Non DM group with p = 0.805 (p <0.05); (4) Relationship between GD and VT (r = 0.220), GD with VCI (r = 0.308), GD with VCE (r = -0.110), GD with VKP (r = 0.219). So it was concluded that there was a positive relationship between GD and VT, VCI, VKP and also there was a negative relationship between GD and VCE. Suggestion: DM sufferers need to conduct routine checks so that health remains well controlled